2001
DOI: 10.1203/00006450-200104000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Exerts Additional Toxic Effects in Hypoxic Cultured Neurons from the Developing Rat Brain by the Recruitment of Glutamate Neurotoxicity

Abstract: Both hypoxia and bilirubin are common risk factors in newborns, which may act synergistically to produce anatomical and functional disturbances of the CNS. Using primary cultures of neurons from the fetal rat brain, it was recently reported that neuronal apoptosis accounts for the deleterious consequences of these two insults. To investigate the influence of hypoxia, bilirubin, or their combination on the outcome of neuronal cells of the immature brain, and delineate cellular mechanisms involved, 6-d-old cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 55 publications
1
11
1
1
Order By: Relevance
“…One of the 12 papers selected one was done only at a single B F value of 0.5 M in the absence of albumin (13), and in part duplicated data from another paper by the same group (14) that was performed over a range of B F values. In another selected paper (15), studies were done at B F values below 5 M, but no toxicity was observed at B F values Յ 1 M. In three of the papers selected (13,14,16), the stock UCB solution was markedly supersaturated, so that precipitation and degradation likely occurred; thus, the true threshold for UCB toxicity may have been lower than the calculated B F values.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the 12 papers selected one was done only at a single B F value of 0.5 M in the absence of albumin (13), and in part duplicated data from another paper by the same group (14) that was performed over a range of B F values. In another selected paper (15), studies were done at B F values below 5 M, but no toxicity was observed at B F values Յ 1 M. In three of the papers selected (13,14,16), the stock UCB solution was markedly supersaturated, so that precipitation and degradation likely occurred; thus, the true threshold for UCB toxicity may have been lower than the calculated B F values.…”
Section: Methodsmentioning
confidence: 99%
“…In another selected paper (15), studies were done at B F values below 5 M, but no toxicity was observed at B F values Յ 1 M. In three of the papers selected (13,14,16), the stock UCB solution was markedly supersaturated, so that precipitation and degradation likely occurred; thus, the true threshold for UCB toxicity may have been lower than the calculated B F values. Another selected paper studied B F values below 5 M, but there were no studies done at B F values between 383 and 1761 nM, so that the true threshold could not be evaluated (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigators performed the majority of analyses of bilirubin-induced apoptosis at a bilirubin: albumin molar ratio of 3, 64 using concentrations at which bilirubin would be anticipated to precipitate from solution. 20 Moreover, as opposed to bilirubin-mediated neuronal cell death, which is triggered by stimulation of the NMDA receptor 66 and prevented by NMDA receptor antagonists, 22 both glutamate and NMDA inhibitors reduce the viability of HT29 adenocarcinoma cells. 67 These disparities in the cellular response may be a result of nonphysiologic concentrations of bilirubin utilized or, alternatively, may reflect distinct mechanisms of bilirubin action in different cell lines.…”
Section: Effect Of Bilirubin On the Permeability Of Isolated Mitochonmentioning
confidence: 99%
“…The apoptotic process involves caspase activation and requires the participation of glutamatergic N-methyl-D-aspartate receptors. Moreover, UCB enhanced the effects of hypoxia in these immature neurons by facilitating glutamate-mediated apoptosis (Grojean et al, 2001). On the other hand, UCB inhibited glutamate uptake in cultured rat cortical astrocytes, which play a major role in the transport of synaptically released glutamate (Silva et al, 1999).…”
mentioning
confidence: 99%